Pengaruh DPK dan LDR Terhadap Penyaluran KUR UMKM dengan NPL Sebagai Variabel Moderasi - Dewi Fitri Kusumawati; Linda Ariany Mahastanti (Politeknik Ganesha Medan, 2023)
This study aims to determine the effect of Third Party Funds (DPK) and Loan to Deposit Ratio (LDR) on MSME KUR distribution with Non-Performing Loans (NPL) as a moderating variable at BUMN Banks distributing MSME KUR. This study used a purposive sampling method, and 4 BUMN Banks were distributing KUR UMKM that met the sample criteria. This study uses secondary data from annual financial reports of 4 state-owned banks and a web related to people's business loans for 2012 – 2022. The data processing method in this study is panel data regression analysis and Moderated Regression Analysis (MRA) using the Eviews 12 program. Based on the results of the research, it shows that DPK affects the distribution of MSME KUR, LDR has no effect on MSME KUR distribution, NPL affects MSME KUR distribution, NPL weakens the relationship between DPK and MSME KUR distribution, and NPL weakens the LDR relationship with MSME KUR distribution.